The Non-Linear Relationship between Corporate Social Responsibility Practices and Financial Performance in Vietnam - Thi Cam Thanh Tran; Thi My Tu Le; Xuan Quynh Le (My University, 2024)
The Non-Linear Relationship between Corporate Social Responsibility Practices and Financial Performance in Vietnam
Keywords: CSR practices; Financial performance; Vietnam